Modelling and analysis of thermal and stress loads in train disc brakes - braking from 250 km/h to standstill - Reibenschuh, Marko (Strojniški vestnik, 2009)
Thermal and stress analysis of disc brakes under specific loads (driving downhill and braking to a standstill) was calculated. The FEM (Finite Element Method) was used to carry out the analysis. The analysis dealt with centrifugal load for two cases of braking, braking to a standstill on a flat surface and braking downhill, maintaining constant speed and afterwards braking to a standstill. The main boundary condition in both cases was the entered heat flux on the braking surface of the disc and the force of the brake clamps. Two different discs were used, one brand new (unused) and one with permitted wearing.
Keywords: vlaki; lokomotive; zavorni diski; temperatura; trdnost; napetost